The Effect of Competency and Training on Employee Performance Through Job Satisfaction - Zulkifly Hijaz; Yana Fajriah; Zulfikri Sukarno (Manunggal Halim Jaya, 2025)
The Effect of Competence and Training on Employee Performance Through Job Satisfaction at UPT Asrama Haji Makassar, supervised by Yana Fajriah and Zulfikri Sukarno. This study aims to analyze the effect of competence and training on employee performance with job satisfaction as a mediating variable at UPT Asrama Haji Makassar. The research employed a quantitative approach with an explanatory research design. Data were collected through questionnaires from 128 respondents and analyzed using Structural Equation Modeling (SEM-PLS) with Smart-PLS software. The findings reveal that competence has no significant effect on either performance or job satisfaction, nor through job satisfaction as a mediator. In contrast, training significantly influences both performance and job satisfaction, as well as indirectly affects performance through partial mediation by job satisfaction. Furthermore, job satisfaction significantly contributes to improving employee performance. Therefore, training and job satisfaction are identified as strategic factors in enhancing employee performance, while competence does not provide a significant contribution as initially assumed.